DETECTION OF JAK2 V617F MUTATION IN A PATIENT WITH C-KIT POSITIVE GASTROINTESTINAL STROMAL TUMOR: CASE REPORT - Trajkova, Sanja; Krstevska Balkanov, Svetlana; Pivkova Veljanovska, Aleksandra; Lichoska-Josifovikj, Fana; Popova-Labacevska, Marija; Ridova, Nevenka; Stojanovska Jakimovska, Simona; Cadievski, Lazar; Cvetanovski, Milce; Kocoski, Bozidar; Paunovska, Andrea; Stojanovski, Martin; et al. (Journal of Morphological Sciences, 2025)
C-Kit is receptor tyrosine kinase which is involved in various  signaling pathways and has been  recognized in pathogenesis of several types of cancers including gastrointestinal stromal tumor (GIST). More than 50 years, scientist have been studied GIST and made advances in treatment based on c-Kit inhibition.    One of the signaling pathway involving activation  via  c-Kit is the JAK/STAT pathway located on hematopoietic cells resulting activation of transcription of a variety of genes.  Here, we provide a case report of patient with two malignancy c-Kit positive GIST and Essential Thrombocytemia (ET) positive for JAK2 V617F mutation. Keywords: c-Kit, GIST, JAK2 V617F mutation, ET.